Complement inhibition for the treatment of COVID-19 triggered thrombotic microangiopathy with cardiac failure: a case report. Issue 10 (28th September 2021) - Utebay, Didar; Seeger, Harald; Müller, Antonia M S; David, Sascha
Abstract: Background: Severe coronavirus disease 2019 (COVID-19) has been increasingly recognized as a multisystem disease. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can infect literally any cell type that expresses its target receptor angiotensin-converting enzyme 2. However, COVID-19-associated organ dysfunction is not only mediated by direct viral effects but also by the interaction between the host's immune response, endotheliopathy, and microvascular coagulopathy. It has been proposed that the activation of the complement system plays a central role in the pathophysiology of severe COVID-19 and the associated endotheliopathy. Case summary: A 76-year-old male patient with indeterminate cardiogenic shock in the setting of confirmed SARS-CoV-2 infection was admitted to our intensive care unit. Coronary angiography did not reveal a plausible explanation for his symptoms. The patient developed renal failure, neurological symptoms, severe thrombocytopenia, and a Coombs-negative haemolytic anaemia with schistocytes. All together the clinical picture was highly suggestive of a thrombotic microangiopathy (TMA) with microvascular cardiac involvement. Conventional therapeutic strategies including high-dose steroids and seven sessions of therapeutic plasma exchange were all unsuccessful. Interestingly, complement inhibition with Eculizumab as rescue approach led to a rapid clinical and laboratory improvement and the patients were discharged with normalized organ functions at Day 36. Conclusion: The aetiology of cardiogenic shock observed in this patient cannot simply be explained by his focal and chronic coronary findings. Although viral myocarditis was not formally excluded, both the clinical features of TMA and the rapid resolution of all clinical signs and symptoms after pharmacological complement inhibition suggest a SARS-CoV-2-driven microangiopathic origin of heart failure.